2021
DOI: 10.3390/nu13124360
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Association of the Portfolio Diet with All-Cause and Cause-Specific Mortality Risk in the Mr. OS and Ms. OS Study

Abstract: The Portfolio Diet has demonstrated its cardiovascular benefit from interventions, but the association between Portfolio Diet adherence and the risk of all-cause and cause-specific mortality has not been examined in Chinese population. The present study has collected Portfolio Diet adherence (assessed by food frequency questionnaire), lifestyle factors and mortality status of 3991 participants in the Mr. Osteoporosis (OS) and Ms. OS Study. Cox regression models were used to examine the association between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…It is notable that the individual effects of each food group was not significant in the Cox regression model. As demonstrated by another analysis of the Mr. OS and Ms. OS Study, the adherence to a cholesterol-lowering plant-based dietary pattern (the Portfolio Diet) was associated with a 28% lower risk of all-cause and cancer mortality [ 12 ], which echoes the perspective that nutrients may provide summative health benefits in the context of general dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is notable that the individual effects of each food group was not significant in the Cox regression model. As demonstrated by another analysis of the Mr. OS and Ms. OS Study, the adherence to a cholesterol-lowering plant-based dietary pattern (the Portfolio Diet) was associated with a 28% lower risk of all-cause and cancer mortality [ 12 ], which echoes the perspective that nutrients may provide summative health benefits in the context of general dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed data from a prospective cohort, the Mr. Osteoporosis and Ms. Osteoporosis Study in Hong Kong (Mr. OS and Ms. OS study), and evaluated the associations of food groups with all-cause and cause-specific mortality [ 12 ]. The Mr. OS and Ms. OS study is a prospective cohort study that recruited 4000 community-living Hong Kong Chinese men and women aged at least 65 years in the period 2001–2003 [ 12 ]. The target was to recruit a stratified sample that equally assigned the cohort into three age groups (65–69, 70–74, and ≥75 years).…”
Section: Methodsmentioning
confidence: 99%
“…All studies were conducted in Asia. There were 14 studies conducted in China [ 7 , 29 , 30 , 43 , 50 , 51 , 53 , [57] , [58] , [59] , [60] , [61] , 63 , 65 ], 12 in Japan [ 8 , 26 , 27 , 31 , 34 , 40 , 41 , 45 , 48 , 49 , 56 , 62 ], 5 in Taiwan [ 35 , 39 , 52 , 55 , 66 ], 3 in Singapore [ 32 , 38 , 42 ], 3 in Hong Kong [ 37 , 44 , 47 ], 2 in South Korea [ 28 , 54 ], and 2 in South Asian countries (Bangladesh, India, and Pakistan) [ 46 , 64 ]. All were prospective cohort studies, except for one study which had a nested case–control study design [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…To examine the overall association between dietary patterns and CVD expressed in RR, we combined study-specific effect estimates using the random-effects model, which was chosen to account for between-study variations [ 33 , 36 ]. As studies included in the meta-analysis reported a mixture of equal-sized groups (i.e., tertile/quartile/quintile) [ 7 , 8 , [26] , [27] , [28] , 30 , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] ] and unequal-sized groups (i.e., score categories defined by cutoff points) [ 37 , 44 , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] ], we transformed the effect estimates from each study to a standard scale of effect, facilitating comparison between the RR at top and bottom tertiles, according to the methods described previously [ [67] , [68] , [69] ]. Under a log-normal distribution, the difference in mean between the top and bottom groups of tertile, quartile, and quintile can be expressed by 2.18, 2.54, and 2.80 standard deviation (SD, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The Portfolio Diet is a predominantly plant-based, vegan diet low in saturated fat and cholesterol. The diet is designed to lower total cholesterol and LDL [ 120 , 135 ]. That is, it is a vegetarian diet that includes the consumption of FF.…”
Section: Resultsmentioning
confidence: 99%